Responsive nanogel and preparation method thereof
Through the development of response nanogelry, the internal environment of the tumor is used to promote the release of drugs, solve the problem of insufficient targeted targeted and drug delivery of HIFU treatment, and improve the effect of anti -tumor treatment.
Patent Information
- Application Number
- CN202411897231.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-01-28
AI Technical Summary
The existing HIFU treatment combined with ferrodystrophy is poor in anti-tumor effects, mainly due to the efflux of iron by exosomes secreted by tumor cells, reducing the effect of ferrodystrophy, and the targeting and responsiveness of drug delivery vehicles.
Develop a response nanogelry, which is prepared by aluminization hyaluronic acid and functional hyaluronic acid, combined with ultrasonic crushing and anti -emulsification method to form nanogelry particles, and use low pH and high GSH environment inside the tumor to promote drug release Essence
The stability and tumor targeting of drugs under physiological conditions are realized, and the micro -environment of the tumor is used to promote the release of drugs, enhance the effect of iron death, and improve the effect of anti -tumor treatment.
Smart Images

Figure CN119367391A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, in particular to a responsive nano gel and a preparation method thereof. Background Art
[0002] Breast cancer is the most common and fatal malignant tumor in women, and its incidence rate is increasing year by year. The latest data show that breast cancer is highly prevalent worldwide, with the incidence and mortality rate among women ranking first, of which triple-negative breast cancer accounts for about 15%. Among the existing treatments for breast cancer, although high-intensity focused ultrasound (HIFU) treatment can kill irradiated tumors non-invasively, it still faces the challenges of tumor residue, recurrence, and metastasis. Studies have found that ferroptosis can not only induce tumor cell death, but also enhance the immunogenicity of tumor cells, which is an efficient tumor treatment strategy.
[0003] However, the anti-tumor effect of HIFU combined with ferroptosis is not satisfactory in actual application. The reason is that the exosomes secreted by tumor cells carry Fe 3+ Secretion outside the cell leads to a decrease in intracellular iron content, reducing the effect of ferroptosis. At the same time, under ultrasound stimulation, the secretion of exosomes increases, further leading to the excretion of iron in tumor cells, inhibiting the anti-tumor treatment effect. In the microenvironment inside tumor cells, the pH value in lysosomes and endosomes is acidic (pH4.5-6.5), and there is a high concentration of glutathione (GSH) in the cytoplasm and endosomes / lysosomes. Currently, clinical chemotherapy drugs have poor targeting and poor responsiveness of drug delivery carriers. Therefore, how to solve the targeting and responsiveness of drug delivery, thereby improving the effect of HIFU treatment, has become a major challenge in current research. Summary of the invention
[0004] To this end, the technical problem to be solved by the present invention is to provide a responsive nanogel and a preparation method thereof, so as to prevent the drug from being leaked under physiological conditions, and at the same time achieve tumor targeting and utilize the characteristics of the internal microenvironment of the tumor to promote the release of the drug.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A responsive nanogel includes a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, and the structural formula of the hydrogel is as follows: , where n is 2272-2841.
[0006] A method for preparing a responsive nanogel, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, and the preparation process of the nanogel is as follows: S1. Synthesis of aldehyde-modified hyaluronic acid: mechanically stir an appropriate amount of hyaluronic acid, deionized water and NaH2PO3·2H2O at 25°C for 12 hours to prepare a mixed solution; add sodium periodate to the mixed solution; stir in the dark at 25°C for 12 hours; add ethylene glycol to terminate the reaction for 1 hour; dialyze with a 1.4wDa dialysis bag for 3-4 days to obtain an aldehyde-modified hyaluronic acid solution; S2. Synthesis of functionalized hyaluronic acid: dissolving hyaluronic acid and 3-3'-dithiobis(propionylhydrazide) in 2-(N-morpholinyl)ethanesulfonic acid monohydrate solution in sequence, adding N-hydroxysuccinimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and reacting at room temperature for 24 hours; dialyzing the solution with deionized water for 5 days to obtain functionalized hyaluronic acid; S3. Preparation of nanogel: Through gelation test, 0.5% by mass aldehyde hyaluronic acid solution and 0.5% by mass functionalized hyaluronic acid solution were gelled in a mass ratio of 1:1 for 10-20 minutes. By ultrasonic crushing combined with reverse emulsification method, the aldehyde hyaluronic acid solution and the functionalized hyaluronic acid solution were mixed in an ice bath and then ultrasonically crushed to form nanogel particles. The nanogel aqueous solution was obtained by centrifugation and removal of the oil phase.
[0007] Furthermore, in the ultrasonic crushing combined with the reverse emulsification method, the output power under ice bath conditions is 450w-600w, and the ultrasonic crushing time is 5-20min; The average hydrated particle size of the nanogel is 105.0-418.7 nm, and the dispersion coefficient of the nanogel is 0.158-0.612.
[0008] A method for preparing a responsive nanogel loaded with Fe3O4 nanoparticles, wherein the nanogel comprises a hydrogel prepared from aldehyded hyaluronic acid and functionalized hyaluronic acid. The preparation process of the nanogel loaded with Fe3O4 nanoparticles is as follows: S1. Synthesis of aldehyde-modified hyaluronic acid: mechanically stir an appropriate amount of hyaluronic acid, deionized water and NaH2PO3·2H2O at 25°C for 12 hours to prepare a mixed solution; add sodium periodate to the mixed solution; stir in the dark at 25°C for 12 hours; add ethylene glycol to terminate the reaction for 1 hour; dialyze with a 1.4wDa dialysis bag for 3-4 days to obtain an aldehyde-modified hyaluronic acid solution; S2. Synthesis of functionalized hyaluronic acid: dissolving hyaluronic acid and 3-3'-dithiobis(propionylhydrazide) in 2-(N-morpholinyl)ethanesulfonic acid monohydrate solution in sequence, adding N-hydroxysuccinimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and reacting at room temperature for 24 hours; dialyzing the solution with deionized water for 5 days to obtain functionalized hyaluronic acid; S3. Preparation of nanogel loaded with Fe3O4 nanoparticles. Fe3O4 nanoparticles were added to a 0.5% by mass aldehyded hyaluronic acid solution. The 0.5% by mass aldehyded hyaluronic acid solution containing Fe3O4 nanoparticles and the 0.5% by mass functionalized hyaluronic acid solution were ultrasonically crushed in an ice bath with an output power of 600 W for 20 minutes at a mass ratio of 1:1 by combining ultrasonic crushing with reverse emulsification. The solution was centrifuged and the oil phase was removed to obtain an aqueous solution of nanogel loaded with Fe3O4.
[0009] Furthermore, the particle size of the Fe3O4 nanoparticles is 10 nm, and the mass concentration of the Fe3O4 nanoparticles is 0.25-0.5 mg / ml; The average hydrated particle size of the nanogel carrying Fe3O4 nanoparticles is 199.7-202.7 nm, and the dispersion coefficient of the nanogel carrying Fe3O4 nanoparticles is 0.165-0.186; In the nanogel loaded with Fe3O4 nanoparticles, the drug loading amount of the Fe3O4 nanoparticles is 2%-4%, and the drug loading efficiency of the Fe3O4 nanoparticles is 43%-72%.
[0010] A method for preparing a responsive nanogel loaded with GW4869, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, and the preparation process of the Fe3O4-loaded nanogel is as follows: S1. Synthesis of aldehyde-modified hyaluronic acid: mechanically stir an appropriate amount of hyaluronic acid, deionized water and NaH2PO3·2H2O at 25°C for 12 hours to prepare a mixed solution; add sodium periodate to the mixed solution; stir in the dark at 25°C for 12 hours; add ethylene glycol to terminate the reaction for 1 hour; dialyze with a 1.4wDa dialysis bag for 3-4 days to obtain an aldehyde-modified hyaluronic acid solution; S2. Synthesis of functionalized hyaluronic acid: dissolving hyaluronic acid and 3-3'-dithiobis(propionylhydrazide) in 2-(N-morpholinyl)ethanesulfonic acid monohydrate solution in sequence, adding N-hydroxysuccinimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and reacting at room temperature for 24 hours; dialyzing the solution with deionized water for 5 days to obtain functionalized hyaluronic acid; S3. Preparation of GW4869-loaded nanogel. GW4869 powder was added to a 0.5% by mass aldehyded hyaluronic acid solution. The 0.5% by mass aldehyded hyaluronic acid solution containing GW4869 powder and the 0.5% by mass functionalized hyaluronic acid solution were mixed in a mass ratio of 1:1 by ultrasonic crushing combined with reverse emulsification method. The mixture was ultrasonically crushed for 20 minutes in an ice bath with an output power of 600 W. The oil phase was removed by centrifugation to obtain a GW4869-loaded nanogel aqueous solution.
[0011] Furthermore, the mass concentration of the GW4869 powder is 0.1-0.2 mg / ml; The average hydrated particle size of the nanogel loaded with GW4869 is 200.9-201.8 nm, and the dispersion coefficient of the nanogel loaded with GW4869 is 0.169-0.173; In the GW4869-loaded nanogel, the drug loading amount of GW4869 is 0.2%-2.7%, and the drug loading efficiency of GW4869 is 30%-69.9%.
[0012] A method for preparing a responsive nanogel carrying GW4869 and Fe3O4 nanoparticles, wherein the nanogel comprises a hydrogel prepared from aldehyded hyaluronic acid and functionalized hyaluronic acid. The preparation process of the nanogel carrying GW4869 and Fe3O4 nanoparticles is as follows: S1. Synthesis of aldehyde-modified hyaluronic acid: mechanically stir an appropriate amount of hyaluronic acid, deionized water and NaH2PO3·2H2O at 25°C for 12 hours to prepare a mixed solution; add sodium periodate to the mixed solution; stir in the dark at 25°C for 12 hours; add ethylene glycol to terminate the reaction for 1 hour; dialyze with a 1.4wDa dialysis bag for 3-4 days to obtain an aldehyde-modified hyaluronic acid solution; S2. Synthesis of functionalized hyaluronic acid: dissolving hyaluronic acid and 3-3'-dithiobis(propionylhydrazide) in 2-(N-morpholinyl)ethanesulfonic acid monohydrate solution in sequence, adding N-hydroxysuccinimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and reacting at room temperature for 24 hours; dialyzing the solution with deionized water for 5 days to obtain functionalized hyaluronic acid; S3. Preparation of nanogels loaded with GW4869 and Fe3O4 nanoparticles. Fe3O4 nanoparticles and GW4869 powder were added to a 0.5% by mass aldehyde hyaluronic acid solution. GW4869 powder was added to a 0.5% by mass functionalized hyaluronic acid solution. The aldehyde hyaluronic acid solution and the functionalized hyaluronic acid solution were ultrasonically crushed in an ice bath with an output power of 600 W for 20 minutes at a mass ratio of 1:1 by combining ultrasonic crushing with reverse emulsification. The nanogels loaded with GW4869 and Fe3O4 nanoparticles were obtained by centrifugation and removal of the oil phase.
[0013] The technical solution of the present invention achieves the following beneficial technical effects: Hyaluronic acid is modified with hydrazide and aldehyde groups respectively, and the two are combined to form Schiff base bonds to form gel. In view of the low pH and high GSH characteristics of the internal environment of the tumor, the disulfide bonds in the hydrogel compound are broken under GSH reduction conditions, and GSH is consumed to further promote the ferroptosis process; in addition, the Schiff base bonds in the hydronanogel compound are broken under acidic conditions in the tumor. The dual-responsive nature will promote the disintegration of the hydrogel and release drugs to act on tumor cells, thereby inhibiting the secretion of exosomes by tumor cells, enhancing ferroptosis, and triggering a series of immune effects, thereby improving the anti-tumor effect; finally, by making the hydrogel into a nano-scale carrier, passive targeting of the tumor site can be achieved through the enhanced permeability and retention effect (EPR effect), and active targeting can be achieved by coating the tumor cell membrane on its surface. The nanogel can enter the tumor cell by endocytosis; in terms of treatment methods, the nanogel can be used to deliver drugs through intravenous injection to solve the problem of iron excretion in residual cancer cells caused by HIFU treatment, thereby improving the effect of HIFU tumor treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A schematic diagram of the structure of a responsive nanogel of the present invention; Figure 2 A schematic diagram of the therapeutic principle of a responsive nanogel of the present invention; Figure 3 Schematic diagram of infrared spectra of hyaluronic acid, aldehyde-modified hyaluronic acid, functionalized hyaluronic acid and hydrogel in a method for preparing responsive nanogel of the present invention; Figure 4 A schematic diagram of the functionalized hyaluronic acid NMR hydrogen spectrum of a method for preparing a responsive nanogel of the present invention; Figure 5 A schematic diagram of a gelation test of a method for preparing a responsive nanogel according to the present invention; Figure 6Schematic diagram of Zeta potential of Example 2, cell membrane nanovesicles, Example 10, Example 11, and Example 12 of a method for preparing a responsive nanogel of the present invention; Figure 7 A schematic diagram comparing the hydrated particle sizes of Example 2, cell membrane nanovesicles, Example 10, Example 11, and Example 12 of a method for preparing a responsive nanogel of the present invention; Figure 8 Transmission electron microscope schematic diagrams of Example 2 and Example 11 of a method for preparing a responsive nanogel of the present invention; Fig. 9 A transmission electron microscope and element mapping schematic diagram of Example 10 of a method for preparing a responsive nanogel of the present invention; Wherein a is a transmission electron microscope image loaded with Fe3O4 nanoparticles, b is an enlarged image of the nanoparticles at A in a, c is a nitrogen element analysis image in b, d is an oxygen element analysis image in b, and e is an iron element analysis image in b; Fig.10 A schematic diagram of a nanogel responsiveness-rheology test of a method for preparing a responsive nanogel according to the present invention; Fig.11 A transmission electron microscope schematic diagram of the responsiveness of a nanogel in a method for preparing a responsive nanogel of the present invention. DETAILED DESCRIPTION
[0015] A responsive nanogel includes a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, wherein the chemical formula of the hydrogel is as follows: , where n is between 2272 and 2841.
[0016] Hyaluronic acid (HA) is modified with hydrazide and aldehyde respectively to obtain aldehyde-modified hyaluronic acid and functionalized hyaluronic acid. The two are combined to form Schiff base bonds to form a gel. In view of the low pH and high GSH (glutathione) characteristics of the internal environment of the tumor, the disulfide bonds in the hydrogel compound are broken under GSH reducing conditions, and GSH is consumed to further promote the ferroptosis process. In addition, the Schiff base bonds in the hydrogel compound are broken under acidic conditions in the tumor. The dual-responsive nature will promote the disintegration of the hydrogel and release drugs to act on tumor cells, thereby inhibiting the secretion of exosomes by tumor cells, enhancing ferroptosis, and triggering a series of immune effects, thereby improving the anti-tumor effect.
[0017] like Figure 1 As shown, by making the hydrogel into a nanoscale carrier, combined with Figure 2, passive targeting of tumor sites can be achieved through the EPR effect (enhanced permeability and retention effect), and active targeting can be achieved by coating the tumor cell membrane on its surface. Nanogels can enter tumor cells through endocytosis. In terms of treatment methods, drugs can be delivered through intravenous nanogels to solve the problem of iron excretion from residual cancer cells caused by HIFU treatment, thereby improving the effect of HIFU tumor treatment.
[0018] A method for preparing a responsive nanogel, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, and the preparation process of the nanogel is as follows: S1. Synthesis of aldehyde-modified hyaluronic acid: mechanically stir an appropriate amount of hyaluronic acid, deionized water and NaH2PO3·2H2O at 25°C for 12 hours to prepare a mixed solution; add sodium periodate to the mixed solution; stir in the dark at 25°C for 12 hours; add ethylene glycol to terminate the reaction for 1 hour; dialyze with a 1.4wDa dialysis bag for 3-4 days to obtain an aldehyde-modified hyaluronic acid solution; S2. Synthesis of functionalized hyaluronic acid: dissolving hyaluronic acid and 3-3'-dithiobis(propionylhydrazide) in 2-(N-morpholinyl)ethanesulfonic acid monohydrate solution in sequence, adding N-hydroxysuccinimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and reacting at room temperature for 24 hours; dialyzing the solution with deionized water for 5 days to obtain functionalized hyaluronic acid; S3. Preparation of nanogel: Through gelation test, 0.5% by mass aldehyde hyaluronic acid solution and 0.5% by mass functionalized hyaluronic acid solution were gelled in a mass ratio of 1:1 for 10-20 minutes. By ultrasonic crushing combined with reverse emulsification method, the aldehyde hyaluronic acid solution and the functionalized hyaluronic acid solution were mixed in an ice bath and then ultrasonically crushed to form nanogel particles. The nanogel aqueous solution was obtained by centrifugation and removal of the oil phase.
[0019] Figure 3 The infrared spectra of HA (hyaluronic acid), HA-CHO (aldehyded hyaluronic acid), HA-DPH (functionalized hyaluronic acid), and GEL (hydrogel) are shown below. Figure 3 The vibration of the C=O bond in b will lead to the appearance of a special peak, usually at 1850-1630cm -1 Position, 1733cm -1 The obvious stretching vibration of the C=O bond at c confirms the success of the aldehyde modification; the amide I band in c usually appears in the wavenumber range of 1690−1630 cm -1 ; in d, 1654cm -1 There is an obvious absorption peak at 1733cm -1The barely visible peaks at 1556 and 1318 cm -1 The obvious CN-absorption of the amide II band indicates the successful implementation of the Schiff base reaction.
[0020] Figure 4 HA-DPH NMR hydrogen spectrum, combined with Figure 4 In HA-DPH, 1 and 3 correspond to CH2, which together correspond to 4 H atoms. In the hydrogen spectrum, they are peaks at around 2.90, and the integrated area is 1.16. Its integral can be used to reflect the content of the product. The characteristic hydrogen signal that can be identified in DPH is CH3 at the 2nd position of the amide, which corresponds to 3 H atoms. It can be used to represent the total amount of hyaluronic acid. Therefore, the grafting rate formula = 0.5*0.5*(A1+A3) / 0.33*(A2), that is, 0.25*(1.16+1.16) / 0.33*3=58.6%.
[0021] Combination Figure 5 From the gelation test, it was found that the modified hyaluronic acid with a mass fraction of 0.5% gelated within 10-20 minutes, which provided a time basis for the preparation of nanogel experiments.
[0022] Example 1 A method for preparing a responsive nanogel, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, and the preparation process of the nanogel is as follows: S1. Synthesis of aldehyded hyaluronic acid (HA-CHO): 2.0 g HA (hyaluronic acid), 100 ml deionized water, and 3.12 g NaH2PO3·2H2O (sodium dihydrogen phosphate, dihydrate) were mechanically stirred at 25°C for 12 hours, 1.08 g NaIO4 (sodium periodate) was added to the above solution, stirred at 25°C in the dark for 12 hours, 2 ml ethylene glycol was added to terminate the reaction for 1 hour, dialyzed with a 1.4 wDa dialysis bag for 3-4 days, and then freeze-dried; S2. Synthesis of functionalized hyaluronic acid (HA-DPH): 400 mg HA (hyaluronic acid) and 1700 mg DPH (3-3'-dithiobis(propionylhydrazide)) were dissolved in 100 ml MES (2-(N-morpholinyl)ethanesulfonic acid monohydrate) solution, 35 mg NHS (N-hydroxysuccinimide) and 288 mg EDCI (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) were added, and the mixture was reacted at room temperature for 24 hours. The solution was dialyzed with deionized water for 5 days (1.4 wDa) and then freeze-dried. S3. Preparation of nanogel. Through gelation test, it was obtained that HA-CHO solution and HA-DPH solution with a mass fraction of 0.5% and a mass ratio of 1:1 gelled in 10-20 minutes. In order to prepare nano-scale gel, ultrasonic crushing + reverse emulsification method was adopted. The two were mixed under ice bath conditions with an output power of 450W and then ultrasonically crushed for 20 minutes (2s super, 1s stop, 1min, interval 1min, a total of 8-10 times). Ultrasonic crushing made the droplet particles in the oil phase fully broken and smaller, and increased the contact between HA-CHO and HA-DPH, thereby forming nanogel particles with relatively uniform particle size. By centrifugation and removing the oil phase, a nanogel aqueous solution with an average hydrated particle size of 308.1 nm (PDI: 0.238) was obtained.
[0023] Example 2 A method for preparing a responsive nanogel, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, and the preparation process of the nanogel is as follows: S1. Synthesis of aldehyde-modified hyaluronic acid (HA-CHO): 2.0 g HA (hyaluronic acid), 100 ml deionized water, and 3.12 g NaH2PO3·2H2O (sodium dihydrogen phosphate, dihydrate) were mechanically stirred at 25°C for 12 hours, 1.08 g NaIO4 (sodium periodate) was added to the above solution, stirred at 25°C in the dark for 12 hours, 2 ml ethylene glycol was added to terminate the reaction for 1 hour, dialyzed with a 1.4 wDa dialysis bag for 3-4 days, and then freeze-dried; S2. Synthesis of functionalized hyaluronic acid (HA-DPH): 400 mg HA (hyaluronic acid) and 1700 mg DPH (3-3'-dithiobis(propionylhydrazide)) were dissolved in 100 ml MES (2-(N-morpholinyl)ethanesulfonic acid monohydrate) solution, 35 mg NHS (N-hydroxysuccinimide) and 288 mg EDCI (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) were added, and the mixture was reacted at room temperature for 24 hours. The solution was dialyzed with deionized water for 5 days (1.4 wDa) and then freeze-dried. S3. Preparation of nanogel. Through gelation test, it was obtained that HA-CHO solution and HA-DPH solution with a mass fraction of 0.5% and a mass ratio of 1:1 gelled in 10-20 minutes. In order to prepare nano-scale gel, ultrasonic crushing + reverse emulsification method was adopted. The two were mixed in an ice bath with an output power of 600W and then ultrasonically crushed for 20 minutes (2s super, 1s stop, 1min, interval 1min, a total of 8-10 times). Ultrasonic crushing made the droplet particles in the oil phase fully broken and smaller, and increased the contact between HA-CHO and HA-DPH, thereby forming nanogel particles with relatively uniform particle size. By centrifugation and removing the oil phase, a nanogel aqueous solution with an average hydrated particle size of 105.0nm (PDI: 0.158) was obtained.
[0024] Example 3 A method for preparing a responsive nanogel, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, and the preparation process of the nanogel is as follows: S1. Synthesis of aldehyded hyaluronic acid (HA-CHO): 2.0 g HA (hyaluronic acid), 100 ml deionized water, and 3.12 g NaH2PO3·2H2O (sodium dihydrogen phosphate, dihydrate) were mechanically stirred at 25°C for 12 hours, 1.08 g NaIO4 (sodium periodate) was added to the above solution, stirred at 25°C in the dark for 12 hours, 2 ml ethylene glycol was added to terminate the reaction for 1 hour, dialyzed with a 1.4 wDa dialysis bag for 3-4 days, and then freeze-dried; S2. Synthesis of functionalized hyaluronic acid (HA-DPH): 400 mg HA (hyaluronic acid) and 1700 mg DPH (3-3'-dithiobis(propionylhydrazide)) were dissolved in 100 ml MES (2-(N-morpholinyl)ethanesulfonic acid monohydrate) solution, 35 mg NHS (N-hydroxysuccinimide) and 288 mg EDCI (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) were added, and the mixture was reacted at room temperature for 24 hours. The solution was dialyzed with deionized water for 5 days (1.4 wDa) and then freeze-dried. S3. Preparation of nanogel. Through gelation test, it was obtained that HA-CHO solution and HA-DPH solution with a mass fraction of 1% gelled in 3-5 minutes at a mass ratio of 1:1. In order to prepare nano-scale gel, ultrasonic crushing + reverse emulsification method was adopted. The two were mixed in an ice bath with an output power of 600W and then ultrasonically crushed for 5 minutes (2s super, 1s stop, 1min, interval 1min, a total of 3 times) to break up the droplets in the oil phase and make them smaller, and increase the contact between HA-CHO and HA-DPH. By centrifugation and removing the oil phase, a nanogel aqueous solution with an average hydrated particle size of 418.7nm (PDI: 0.612) was obtained. The gel monomer solution with a mass fraction of 1% may form a nanogel with a relatively uneven particle size due to the excessively fast gelation speed, which resulted in the insufficient crushing of the droplets in the oil phase.
[0025] Example 4 A method for preparing a responsive nanogel, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, and the preparation process of the nanogel is as follows: S1. Synthesis of aldehyded hyaluronic acid (HA-CHO): 2.0 g HA (hyaluronic acid), 100 ml deionized water, and 3.12 g NaH2PO3·2H2O (sodium dihydrogen phosphate, dihydrate) were mechanically stirred at 25°C for 12 hours, 1.08 g NaIO4 (sodium periodate) was added to the above solution, stirred at 25°C in the dark for 12 hours, 2 ml ethylene glycol was added to terminate the reaction for 1 hour, dialyzed with a 1.4 wDa dialysis bag for 3-4 days, and then freeze-dried; S2. Synthesis of functionalized hyaluronic acid (HA-DPH): 400 mg HA (hyaluronic acid) and 1700 mg DPH (3-3'-dithiobis(propionylhydrazide)) were dissolved in 100 ml MES (2-(N-morpholinyl)ethanesulfonic acid monohydrate) solution, 35 mg NHS (N-hydroxysuccinimide) and 288 mg EDCI (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) were added, and the mixture was reacted at room temperature for 24 hours. The solution was dialyzed with deionized water for 5 days (1.4 wDa) and then freeze-dried. S3. Preparation of nanogel. Through gelation test, it was obtained that HA-CHO solution and HA-DPH solution with a mass fraction of 0.5% gelled in 5-10 minutes at a mass ratio of 1:2. In order to prepare nano-scale gel, ultrasonic crushing + reverse emulsification method was adopted. The two were mixed in an ice bath with an output power of 600W and then ultrasonically crushed for 20 minutes (2s super, 1s stop, 1min, interval 1min, a total of 4-6 times) to break up the droplets in the oil phase and reduce them, and increase the contact between HA-CHO and HA-DPH. By centrifugation and removing the oil phase, a nanogel aqueous solution with an average hydrated particle size of 312.6nm (PDI: 0.409) was obtained.
[0026] Example 5 A method for preparing a responsive nanogel, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, and the preparation process of the nanogel is as follows: S1. Synthesis of aldehyded hyaluronic acid (HA-CHO): 2.0 g HA (hyaluronic acid), 100 ml deionized water, and 3.12 g NaH2PO3·2H2O (sodium dihydrogen phosphate, dihydrate) were mechanically stirred at 25°C for 12 hours, 1.08 g NaIO4 (sodium periodate) was added to the above solution, stirred at 25°C in the dark for 12 hours, 2 ml ethylene glycol was added to terminate the reaction for 1 hour, dialyzed with a 1.4 wDa dialysis bag for 3-4 days, and then freeze-dried; S2. Synthesis of functionalized hyaluronic acid (HA-DPH): 400 mg HA (hyaluronic acid) and 1700 mg DPH (3-3'-dithiobis(propionylhydrazide)) were dissolved in 100 ml MES (2-(N-morpholinyl)ethanesulfonic acid monohydrate) solution, 35 mg NHS (N-hydroxysuccinimide) and 288 mg EDCI (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) were added, and the mixture was reacted at room temperature for 24 hours. The solution was dialyzed with deionized water for 5 days (1.4 wDa) and then freeze-dried. S3. Preparation of nanogel. Through gelation test, it was found that HA-CHO solution and HA-DPH solution with a mass fraction of 0.5% were mixed at a mass ratio of 2:1. They still did not gel after 60 minutes. Because their gelation time was too long, this mass fraction and this ratio were not considered for the preparation of nanogel.
[0027] In combination with Examples 1-5, by changing the ratio of the gel monomer solution, it was found that under the same mass fraction but different gel ratios, the gelation time was different. Increasing the proportion of DPH shortened the gelation time. Without changing other ultrasonic parameters and only changing the time, the average hydrated particle size and the dispersion coefficient PDI showed different effects. For example, in Example 3, under this condition, the droplets in the oil phase were not fully broken up, possibly because the nanogel gelation speed was too fast, forming a nanogel with a relatively uneven particle size and not small enough.
[0028] Example 6 A method for preparing a nanogel carrying Fe3O4 nanoparticles, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid. The preparation process of the nanogel carrying Fe3O4 nanoparticles is as follows: S1. Synthesis of aldehyded hyaluronic acid (HA-CHO): 2.0 g HA (hyaluronic acid), 100 ml deionized water, and 3.12 g NaH2PO3·2H2O (sodium dihydrogen phosphate, dihydrate) were mechanically stirred at 25°C for 12 hours, 1.08 g NaIO4 (sodium periodate) was added to the above solution, stirred at 25°C in the dark for 12 hours, 2 ml ethylene glycol was added to terminate the reaction for 1 hour, dialyzed with a 1.4 wDa dialysis bag for 3-4 days, and then freeze-dried; S2. Synthesis of functionalized hyaluronic acid (HA-DPH): 400 mg HA (hyaluronic acid) and 1700 mg DPH (3-3'-dithiobis(propionylhydrazide)) were dissolved in 100 ml MES (2-(N-morpholinyl)ethanesulfonic acid monohydrate) solution, 35 mg NHS (N-hydroxysuccinimide) and 288 mg EDCI (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) were added, and the mixture was reacted at room temperature for 24 hours. The solution was dialyzed with deionized water for 5 days (1.4 wDa) and then freeze-dried. S3. Preparation of nanogel: Fe3O4 nanoparticles (10 nm, 0.5 mg / ml) were added to 0.5% HA-CHO solution, and 0.5% HA-CHO solution (containing Fe3O4 nanoparticles, 10 nm, 0.5 mg / ml) and HA-DPH solution were mixed at a mass ratio of 1:1. Ultrasonication + reverse emulsification method was used, and ultrasonication was performed for 20 min (2 s on, 1 s off) in an ice bath with an output power of 600 W. , 1min, 1min interval, a total of 8-10 times), ultrasonic crushing made the droplet particles in the oil phase fully broken and smaller, and increased the contact between HA-CHO, HA-DPH and Fe3O4 nanoparticles, thereby forming nanogel particles with relatively uniform particle size. By centrifugation and removing the oil phase, a nanogel aqueous solution with an average hydrated particle size of 202.7nm (PDI: 0.165) was obtained. Atomic absorption spectroscopy showed that the drug loading capacity and drug loading efficiency of Fe3O4 nanoparticles were 4% and 72%, respectively.
[0029] Example 7 A method for preparing a nanogel loaded with Fe3O4 nanoparticles, wherein the nanogel comprises a hydrogel prepared from aldehyded hyaluronic acid and functionalized hyaluronic acid. The preparation process of the nanogel loaded with Fe3O4 is as follows: S1. Synthesis of aldehyded hyaluronic acid (HA-CHO): 2.0 g HA (hyaluronic acid), 100 ml deionized water, and 3.12 g NaH2PO3·2H2O (sodium dihydrogen phosphate, dihydrate) were mechanically stirred at 25°C for 12 hours, 1.08 g NaIO4 (sodium periodate) was added to the above solution, stirred at 25°C in the dark for 12 hours, 2 ml ethylene glycol was added to terminate the reaction for 1 hour, dialyzed with a 1.4 wDa dialysis bag for 3-4 days, and then freeze-dried; S2. Synthesis of functionalized hyaluronic acid (HA-DPH): 400 mg HA (hyaluronic acid) and 1700 mg DPH (3-3'-dithiobis(propionylhydrazide)) were dissolved in 100 ml MES (2-(N-morpholinyl)ethanesulfonic acid monohydrate) solution, 35 mg NHS (N-hydroxysuccinimide) and 288 mg EDCI (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) were added, and the mixture was reacted at room temperature for 24 hours. The solution was dialyzed with deionized water for 5 days (1.4 wDa) and then freeze-dried. S3. Add Fe3O4 nanoparticles (10 nm, 0.25 mg / ml) into 0.5% HA-CHO solution by mass, mix 0.5% HA-CHO solution (containing Fe3O4 nanoparticles, 10 nm, 0.25 mg / ml) and HA-DPH solution by mass ratio of 1:1, adopt ultrasonic crushing + reverse emulsification method, set the output power to 600 W and carry out ultrasonic crushing for 20 minutes in ice bath condition (2 seconds of ultrasonic crushing, 1 second of stopping, 1 minute of ultrasonic crushing, 1 minute of interval, a total of 8-10 times of ultrasonic crushing), so that the droplet particles in the oil phase are fully crushed and reduced, and the contact between HA-CHO, HA-DPH and Fe3O4 nanoparticles is increased, so as to form nanogel particles with relatively uniform particle size. By centrifuging and removing the oil phase, a nanogel aqueous solution with an average hydrated particle size of 199.7 nm (PDI: 0.186) was obtained. Atomic absorption spectroscopy showed that the drug loading capacity and drug loading efficiency of Fe3O4 nanoparticles were 2% and 43%, respectively.
[0030] Example 8 A method for preparing a nanogel loaded with GW4869, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid. The preparation process of the nanogel loaded with GW4869 is as follows: S1. Synthesis of aldehyded hyaluronic acid (HA-CHO): 2.0 g HA (hyaluronic acid), 100 ml deionized water, and 3.12 g NaH2PO3·2H2O (sodium dihydrogen phosphate, dihydrate) were mechanically stirred at 25°C for 12 hours, 1.08 g NaIO4 (sodium periodate) was added to the above solution, stirred at 25°C in the dark for 12 hours, 2 ml ethylene glycol was added to terminate the reaction for 1 hour, dialyzed with a 1.4 wDa dialysis bag for 3-4 days, and then freeze-dried; S2. Synthesis of functionalized hyaluronic acid (HA-DPH): 400 mg HA (hyaluronic acid) and 1700 mg DPH (3-3'-dithiobis(propionylhydrazide)) were dissolved in 100 ml MES (2-(N-morpholinyl)ethanesulfonic acid monohydrate) solution, 35 mg NHS (N-hydroxysuccinimide) and 288 mg EDCI (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) were added, and the mixture was reacted at room temperature for 24 hours. The solution was dialyzed with deionized water for 5 days (1.4 wDa) and then freeze-dried. S3. Add GW4869 powder (0.1 mg / ml) into HA-CHO solution with a mass fraction of 0.5%, mix HA-CHO solution (containing GW4869, 0.1 mg / ml) and HA-DPH solution with a mass fraction of 0.5% at a mass ratio of 1:1, adopt ultrasonic crushing + reverse emulsification method, set the output power to 600W and perform ultrasonic crushing for 20 minutes under ice bath conditions (2 seconds of supersonication, 1 second of stop, 1 minute, 1 minute interval, a total of 8-10 times of supersonication), ultrasonic crushing makes the droplet particles in the oil phase fully crushed and smaller, and increases the contact between HA-CHO containing GW4869 and HA-DPH, thereby forming nanogel particles with relatively uniform particle size, and obtain nanogel aqueous solution with an average hydrated particle size of 200.9 nm (PDI: 0.173) by centrifugation and removal of the oil phase, and the drug loading amount and drug loading efficiency of GW4869 are 0.2% and 30%, respectively, as measured by ultraviolet spectrophotometer.
[0031] Example 9 A method for preparing a nanogel loaded with GW4869, wherein the nanogel comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid. The preparation process of the nanogel loaded with GW4869 is as follows: S1. Synthesis of aldehyded hyaluronic acid (HA-CHO): 2.0 g HA (hyaluronic acid), 100 ml deionized water, and 3.12 g NaH2PO3·2H2O (sodium dihydrogen phosphate, dihydrate) were mechanically stirred at 25°C for 12 hours, 1.08 g NaIO4 (sodium periodate) was added to the above solution, stirred at 25°C in the dark for 12 hours, 2 ml ethylene glycol was added to terminate the reaction for 1 hour, dialyzed with a 1.4 wDa dialysis bag for 3-4 days, and then freeze-dried; S2. Synthesis of functionalized hyaluronic acid (HA-DPH): 400 mg HA (hyaluronic acid) and 1700 mg DPH (3-3'-dithiobis(propionylhydrazide)) were dissolved in 100 ml MES (2-(N-morpholinyl)ethanesulfonic acid monohydrate) solution, 35 mg NHS (N-hydroxysuccinimide) and 288 mg EDCI (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) were added, and the mixture was reacted at room temperature for 24 hours. The solution was dialyzed with deionized water for 5 days (1.4 wDa) and then freeze-dried. S3, add GW4869 powder (0.2 mg / ml) to HA-CHO solution with a mass fraction of 0.5% and HA-DPH solution with a mass fraction of 0.5% respectively, and mix HA-CHO solution (containing GW4869, 0.2 mg / ml) and HA-DPH solution (containing GW4869, 0.2 The oil phase was mixed with HA-CHO and HA-DPH at a mass ratio of 1:1, and ultrasonic crushing + reverse emulsification method was used. The ultrasonic crushing was performed for 20 minutes under ice bath conditions with an output power of 600 W (2 seconds of ultrasonic crushing, 1 second of stopping, 1 minute of ultrasonic crushing, and 1 minute of interval, for a total of 8-10 times of ultrasonic crushing). The droplet particles in the oil phase were fully crushed and reduced in size by ultrasonic crushing, and the contact between HA-CHO and HA-DPH containing GW4869 was increased, thereby forming nanogel particles with relatively uniform particle size. The nanogel aqueous solution with an average hydrated particle size of 201.8 nm (PDI: 0.169) was obtained by centrifugation and removal of the oil phase. The drug loading amount and drug loading efficiency of GW4869 were 2.7% and 69.9%, respectively, as measured by UV spectrophotometer.
[0032] Example 10 A method for preparing a nanogel carrying GW4869 and Fe3O4 nanoparticles, wherein the nanogel comprises a hydrogel prepared from aldehyded hyaluronic acid and functionalized hyaluronic acid. The preparation process of the nanogel carrying GW4869 and Fe3O4 nanoparticles is as follows: S1. Synthesis of aldehyded hyaluronic acid (HA-CHO): 2.0 g HA (hyaluronic acid), 100 ml deionized water, and 3.12 g NaH2PO3·2H2O (sodium dihydrogen phosphate, dihydrate) were mechanically stirred at 25°C for 12 hours, 1.08 g NaIO4 (sodium periodate) was added to the above solution, stirred at 25°C in the dark for 12 hours, 2 ml ethylene glycol was added to terminate the reaction for 1 hour, dialyzed with a 1.4 wDa dialysis bag for 3-4 days, and then freeze-dried; S2. Synthesis of functionalized hyaluronic acid (HA-DPH): 400 mg HA (hyaluronic acid) and 1700 mg DPH (3-3'-dithiobis(propionylhydrazide)) were dissolved in 100 ml MES (2-(N-morpholinyl)ethanesulfonic acid monohydrate) solution, 35 mg NHS (N-hydroxysuccinimide) and 288 mg EDCI (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) were added, and the mixture was reacted at room temperature for 24 hours. The solution was dialyzed with deionized water for 5 days (1.4 wDa) and then freeze-dried. S3, Fe3O4 nanoparticles (10 nm, 0.5 mg / ml) and GW4869 (0.2 mg / ml) were added to 0.5% HA-CHO solution, and GW4869 (0.2 mg / ml) was added to 0.5% HA-DPH solution. mg / ml), the above solutions were mixed in a mass ratio of 1:1, and ultrasonic crushing + reverse emulsification method was adopted. The ultrasonic crushing was performed for 20 minutes under ice bath conditions with an output power of 600W (2s of ultrasonic crushing, 1s of stopping, 1min of ultrasonic crushing, 1min of interval, a total of 8-10 times of ultrasonic crushing). The ultrasonic crushing made the droplet particles in the oil phase fully crushed and smaller, and increased the contact between HA-CHO (Fe3O4 nanoparticles and GW4869) and HA-DPH (containing GW4869), thereby forming nanogel particles with relatively uniform particle size. By centrifugation and removing the oil phase, a nanogel aqueous solution with an average hydrated particle size of 207.0nm (PDI: 0.178) was obtained. By atomic absorption spectroscopy, the drug loading amount and drug loading efficiency of Fe3O4 nanoparticles were 3.4% and 70%, respectively. By ultraviolet spectrophotometer, the drug loading amount and drug loading efficiency of GW4869 were 2.4% and 68.5%, respectively.
[0033] Embodiment 11 On the basis of Example 2, the prepared nanogel is coated with the cell membrane, and the specific steps are as follows: Extraction and storage of cell membranes: The stored Luc-4T1 cells were thawed and dispersed in deionized water. The Luc-4T1 cells were disrupted by ultrasonic cell disruptor in an ice bath, and the cell fragments were stored at 4°C (1×10 4 g, 30 min) to remove organelles and cell debris, and then ultracentrifugation (1 × 10 5 g, 2 h), the cell membranes were further separated from the supernatant, and the extracted cell membranes were dispersed in phosphate-buffered saline (PBS) and transferred to a −80 °C refrigerator for storage; Nanogel coating of cell membrane: the cell membrane stored in a -80°C refrigerator was thawed, diluted to an appropriate concentration and subjected to ice bath ultrasound, and the cell membrane solution was extruded 20 times in turn through a liposome extruder containing 0.4μm and 0.2μm polycarbonate filter membranes to obtain cell membrane nanovesicles, with an average hydrated particle size of 161nm (PDI: 0.128). The cell membrane nanovesicles and nanogels were mixed in a mass ratio of 1:1 and extruded 20 times through a liposome extruder containing a 0.2μm polycarbonate filter membrane to obtain nanogel coating the cell membrane, with an average hydrated particle size of 166nm (PDI: 0.204).
[0034] Example 12 On the basis of Example 10, the prepared nanogel carrying GW4869 and Fe3O4 nanoparticles was coated on the cell membrane, and the specific steps were as follows: Extraction and storage of cell membrane: The stored Luc-4T1 cells were thawed and dispersed in deionized water. The Luc-4T1 cells were disrupted by ultrasonic cell disruptor in an ice bath. Cell fragments were stored at 4°C (1×10 4 g, 30 min) to remove organelles and cell debris. Then, ultracentrifugation (1 × 10 5 g, 2 h), the cell membranes were further separated from the supernatant, and the extracted cell membranes were dispersed in phosphate-buffered saline (PBS) and transferred to a −80 °C refrigerator for storage; Nanogel coating of cell membrane: the cell membrane stored in a -80°C refrigerator was thawed, diluted to an appropriate concentration and subjected to ice bath ultrasound, and the cell membrane solution was extruded 20 times in turn through a liposome extruder containing 0.4μm and 0.2μm polycarbonate filter membranes to obtain cell membrane nanovesicles, with an average hydrated particle size of 161nm (PDI: 0.128). The cell membrane nanovesicles were mixed with drug-loaded nanogels in a mass ratio of 1:1, and extruded 20 times through a liposome extruder containing a 0.2μm polycarbonate filter membrane to obtain drug-loaded nanogel coating the cell membrane, with an average hydrated particle size of 221nm (PDI: 0.198).
[0035] In summary, in combination with Examples 1-12 Figure 6-Figure 11 , Figure 6 The Zeta potential diagrams are shown in Example 2 (nanogel), cell membrane nanovesicles, Example 10 (loaded with Fe3O4 nanoparticles and GW4869 nanogel), Example 11 (nanogel coating), and Example 12 (loaded with Fe3O4 nanoparticles and GW4869 nanogel coating). It can be seen from the Zeta potential that the Zeta potential of the coated nanogel and the drug-loaded nanogel has changed and is close to the Zeta potential of the cell membrane, indicating that the cell membrane coating is successful.
[0036] Figure 7 It is a comparison diagram of the hydrated particle sizes of Example 2 (nanogel), cell membrane nanovesicles, Example 10 (Fe3O4 and GW4869 nanogel), Example 11 (nanogel coating), and Example 12 (Fe3O4 nanoparticles and GW4869 nanogel coating). From the hydrated particle size diagram, it is obtained: the particle size changes of the unloaded nanogel and the drug-loaded nanogel before and after coating. The increase in particle size after coating indicates the successful coating of the cell membrane.
[0037] Figure 8The TEM (transmission electron microscope) of Example 2 (nanogel) and Example 11 (nanogel coating) shows the successful coating of the cell membrane.
[0038] Fig. 9 The transmission electron microscope and element mapping diagram of Example 10 (loaded with Fe3O4 nanoparticles and GW4869 nanogel) show that the dispersed particle size of the nanoparticles is relatively uniform. The black spots or black masses on it indicate Fe3O4 nanoparticles The loading was successful. b is the elemental analysis of the nanoparticles at A in a. c, d, and e are all transmission electron microscopy images of the nanoparticles in b. Mirror image, The elemental analysis of Example 10 (loaded Fe3O4 nanoparticles and GW4869 nanogel) showed that the Fe3O4 nanoparticles were successfully loaded into the nanogel.
[0039] Fig.10 Figure 3 is a schematic diagram of hydrogel responsiveness-rheological test. From the rheological results, it was found that the storage modulus of the 10 mM glutathione group (simulating the glutathione environment in tumor cells) and the 2.5 mM glutathione group (simulating the glutathione environment in normal cells) were lower than that of the 0.1 mM glutathione group, which may be due to the rupture of the disulfide bonds of the hydrogel under glutathione reduction conditions; and, with the increase of glutathione concentration, the storage modulus of the hydrogel showed a downward trend, and dropped to 208 Pa in the 10 mM glutathione group; the storage modulus of the pH 5.0 group (simulating the acidic environment of lysosomes in tumor cells) and the pH 6.8 group (simulating the tumor tissue microenvironment) were both lower than those of the blank group, which may be due to the responsive rupture of the Schiff base bonds in the hydrogel; and, the storage modulus was the lowest in the pH 5.0 group, dropping to 285 Pa, indicating that the hydrogel responded in both the high glutathione environment and the acidic environment simulating tumor cells.
[0040] Fig.11 This is a TEM image of the responsiveness of the nanogel. After incubation at 37°C in a simulated tumor cell GSH (glutathione) environment (10mM GSH) and an acidic environment (pH5.0), the cross-linking of the nanogel was destroyed. After drying, the HA-DPH and HA-CHO monomers aggregated together to form small particles, demonstrating the responsiveness of the nanogel in the tumor cell microenvironment.
[0041] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A responsive nanogel, characterized in that: The invention comprises a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid, wherein the structural formula of the hydrogel is as follows: , where n is 2272-2841.
2. The responsive nanogel according to claim 1, characterized in that The mass fraction of the aldehyde-modified hyaluronic acid in the hydrogel is 0.5%-1%, the mass fraction of the functionalized hyaluronic acid is 0.5%-1%, and the mass ratio of the aldehyde-modified hyaluronic acid to the functionalized hyaluronic acid is 1:1; The functionalized hyaluronic acid is hydrazide hyaluronic acid modified with 3-3'-dithiobis(propionylhydrazide).
3. A method for preparing a responsive nanogel, characterized in that: The nanogel includes a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid. The preparation process of the nanogel is as follows: S1. Synthesis of aldehyde-modified hyaluronic acid: mechanically stir an appropriate amount of hyaluronic acid, deionized water and NaH2PO3·2H2O at 25°C for 12 hours to prepare a mixed solution; add sodium periodate to the mixed solution; stir in the dark at 25°C for 12 hours; add ethylene glycol to terminate the reaction for 1 hour; dialyze with a 1.4wDa dialysis bag for 3-4 days to obtain an aldehyde-modified hyaluronic acid solution; S2. Synthesis of functionalized hyaluronic acid: dissolving hyaluronic acid and 3-3'-dithiobis(propionylhydrazide) in 2-(N-morpholinyl)ethanesulfonic acid monohydrate solution in sequence, adding N-hydroxysuccinimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and reacting at room temperature for 24 hours; dialyzing the solution with deionized water for 5 days to obtain functionalized hyaluronic acid; S3. Preparation of nanogel: Through gelation test, 0.5% by mass aldehyde hyaluronic acid solution and 0.5% by mass functionalized hyaluronic acid solution were gelled in a mass ratio of 1:1 for 10-20 minutes. By ultrasonic crushing combined with reverse emulsification method, the aldehyde hyaluronic acid solution and the functionalized hyaluronic acid solution were mixed in an ice bath and then ultrasonically crushed to form nanogel particles. The nanogel aqueous solution was obtained by centrifugation and removal of the oil phase.
4. The preparation method according to claim 3, characterized in that: In the ultrasonic crushing combined with the reverse emulsification method, the output power under ice bath conditions is 450w-600w, and the ultrasonic crushing time is 5-20min; The average hydrated particle size of the nanogel is 105.0-418.7 nm, and the dispersion coefficient of the nanogel is 0.158-0.
612.
5. A method for preparing a responsive nanogel loaded with Fe3O4 nanoparticles, characterized in that: The nanogel includes a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid. The preparation process of the nanogel carrying Fe3O4 nanoparticles is as follows: S1. Synthesis of aldehyde-modified hyaluronic acid: mechanically stir an appropriate amount of hyaluronic acid, deionized water and NaH2PO3·2H2O at 25°C for 12 hours to prepare a mixed solution; add sodium periodate to the mixed solution; stir in the dark at 25°C for 12 hours; add ethylene glycol to terminate the reaction for 1 hour; dialyze with a 1.4wDa dialysis bag for 3-4 days to obtain an aldehyde-modified hyaluronic acid solution; S2. Synthesis of functionalized hyaluronic acid: dissolving hyaluronic acid and 3-3'-dithiobis(propionylhydrazide) in 2-(N-morpholinyl)ethanesulfonic acid monohydrate solution in sequence, adding N-hydroxysuccinimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and reacting at room temperature for 24 hours; dialyzing the solution with deionized water for 5 days to obtain functionalized hyaluronic acid; S3. Preparation of nanogel loaded with Fe3O4 nanoparticles. Fe3O4 nanoparticles were added to a 0.5% by mass aldehyded hyaluronic acid solution. The 0.5% by mass aldehyded hyaluronic acid solution containing Fe3O4 nanoparticles and the 0.5% by mass functionalized hyaluronic acid solution were ultrasonically crushed in an ice bath with an output power of 600 W for 20 minutes at a mass ratio of 1:1 by combining ultrasonic crushing with reverse emulsification. The nanogel aqueous solution loaded with Fe3O4 was obtained by centrifugation and removal of the oil phase.
6. The method for preparing the responsive nanogel carrying Fe3O4 nanoparticles according to claim 5, characterized in that: The particle size of the Fe3O4 nanoparticles is 10 nm, and the mass concentration of the Fe3O4 nanoparticles is 0.25-0.5 mg / ml; The average hydrated particle size of the nanogel carrying Fe3O4 nanoparticles is 199.7-202.7 nm, and the dispersion coefficient of the nanogel carrying Fe3O4 nanoparticles is 0.165-0.186; In the nanogel loaded with Fe3O4 nanoparticles, the drug loading amount of the Fe3O4 nanoparticles is 2%-4%, and the drug loading efficiency of the Fe3O4 nanoparticles is 43%-72%.
7. A method for preparing a responsive nanogel loaded with GW4869, characterized in that: The nanogel includes a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid. The preparation process of the Fe3O4-loaded nanogel is as follows: S1. Synthesis of aldehyde-modified hyaluronic acid: mechanically stir an appropriate amount of hyaluronic acid, deionized water and NaH2PO3·2H2O at 25°C for 12 hours to prepare a mixed solution; add sodium periodate to the mixed solution; stir in the dark at 25°C for 12 hours; add ethylene glycol to terminate the reaction for 1 hour; dialyze with a 1.4wDa dialysis bag for 3-4 days to obtain an aldehyde-modified hyaluronic acid solution; S2. Synthesis of functionalized hyaluronic acid: dissolving hyaluronic acid and 3-3'-dithiobis(propionylhydrazide) in 2-(N-morpholinyl)ethanesulfonic acid monohydrate solution in sequence, adding N-hydroxysuccinimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and reacting at room temperature for 24 hours; dialyzing the solution with deionized water for 5 days to obtain functionalized hyaluronic acid; S3. Preparation of GW4869-loaded nanogel. GW4869 powder was added to a 0.5% by mass aldehyded hyaluronic acid solution. The 0.5% by mass aldehyded hyaluronic acid solution containing GW4869 powder and the 0.5% by mass functionalized hyaluronic acid solution were mixed in a mass ratio of 1:1 by ultrasonic crushing combined with reverse emulsification method. The mixture was ultrasonically crushed for 20 minutes in an ice bath with an output power of 600 W. The oil phase was removed by centrifugation to obtain a GW4869-loaded nanogel aqueous solution.
8. The method for preparing the responsive nanogel loaded with GW4869 according to claim 7, characterized in that: The mass concentration of the GW4869 powder is 0.1-0.2 mg / ml; The average hydrated particle size of the nanogel loaded with GW4869 is 200.9-201.8 nm, and the dispersion coefficient of the nanogel loaded with GW4869 is 0.169-0.173; In the GW4869-loaded nanogel, the drug loading amount of GW4869 is 0.2%-2.7%, and the drug loading efficiency of GW4869 is 30%-69.9%.
9. A method for preparing a responsive nanogel carrying GW4869 and Fe3O4 nanoparticles, characterized in that: The nanogel includes a hydrogel prepared from aldehyde-modified hyaluronic acid and functionalized hyaluronic acid. The preparation process of the nanogel loaded with GW4869 and Fe3O4 nanoparticles is as follows: S1. Synthesis of aldehyde-modified hyaluronic acid: mechanically stir an appropriate amount of hyaluronic acid, deionized water and NaH2PO3·2H2O at 25°C for 12 hours to prepare a mixed solution; add sodium periodate to the mixed solution; stir in the dark at 25°C for 12 hours; add ethylene glycol to terminate the reaction for 1 hour; dialyze with a 1.4wDa dialysis bag for 3-4 days to obtain an aldehyde-modified hyaluronic acid solution; S2. Synthesis of functionalized hyaluronic acid: dissolving hyaluronic acid and 3-3'-dithiobis(propionylhydrazide) in 2-(N-morpholinyl)ethanesulfonic acid monohydrate solution in sequence, adding N-hydroxysuccinimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and reacting at room temperature for 24 hours; dialyzing the solution with deionized water for 5 days to obtain functionalized hyaluronic acid; S3. Preparation of nanogels loaded with GW4869 and Fe3O4 nanoparticles. Fe3O4 nanoparticles and GW4869 powder were added to a 0.5% by mass aldehyde hyaluronic acid solution. GW4869 powder was added to a 0.5% by mass functionalized hyaluronic acid solution. The aldehyde hyaluronic acid solution and the functionalized hyaluronic acid solution were ultrasonically crushed in an ice bath with an output power of 600 W for 20 minutes at a mass ratio of 1:1 by combining ultrasonic crushing with reverse emulsification. The nanogels loaded with GW4869 and Fe3O4 nanoparticles were obtained by centrifugation and removal of the oil phase.
Citation Information
Patent Citations
Tumor-targeted T1-T2 double nuclear magnetic resonance imaging contrast agent and preparation method and application thereof
CN104758956A
Injectable intelligent response hydrogel and preparation method and application thereof
CN109966558A
Temperature-sensitive tumor therapeutic agent containing exosome inhibitor and application of temperature-sensitive tumor therapeutic agent
CN117919165A
Digital twin program generating flexible demand resource data
KR1020220057709A